2020
DOI: 10.1140/epjp/s13360-020-00303-0
|View full text |Cite
|
Sign up to set email alerts
|

Scattering and absorption sections of nonlinear electromagnetic black holes

Abstract: The expression of the impact parameter, in the analysis for classical and semiclassical scattering cross sections for black holes, is obtained with nonlinear electrodynamics (NLED) while the absorption section is studied with the sinc approximation in the eikonal limit considering NLED.As an illustration we calculate the classical and semiclassical scattering as well as the absorption sections for three black holes under NLED, the magnetic Bardeen and Bronnikov black holes and the regular Euler-Heisenberg blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Similar behavior was observed in [9] in the study of the Scattering and absorption sections black holes in NED.…”
Section: A Bardeen Black Holesupporting
confidence: 82%
See 1 more Smart Citation
“…Similar behavior was observed in [9] in the study of the Scattering and absorption sections black holes in NED.…”
Section: A Bardeen Black Holesupporting
confidence: 82%
“…Then, the electromagnetic fields modify the trajectories of the null geodesics [7]. The effects of no-linear electrodynamics have been analyzed by various authors to study a variety of physical situations, for example, the quasinormal modes of non-linear electromagnetic black holes [8], the Scattering and absorption sections black hole in NED [9] and the shadow of Bardeen black hole in NED [10] as well as the shadow of Euler-Heisenberg and Bronnikov black holes [11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, within BI NLED, an incomplete list of works studying BH solutions can be found in [127][128][129][130][131][132][133][134][135][136][137][138][139][140][141]. Similar studies within the context of Euler-Heisenberg non-linear electrodynamics can instead be found in [120,[142][143][144][145][146][147][148][149][150]. Of particular interest to us is [142], where it was argued that regular BH solutions are not possible for configurations with non-zero electric charge, under the assumptions of static spherical symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of one-loop nonperturbative QED, the EH Lagrangian attracts to draw more attention to the topic of generalized BH solutions. Many interesting BH studies in the frame of the EH non-linear electrodynamics are presented in [63,[65][66][67][68][69][70][71][72][73][74][75][76]. Among these studies, in [66], it has been shown that for static spherical symmetry spacetime regular BHs are not viable for configurations with non-vanishing electric charge.…”
Section: Introductionmentioning
confidence: 99%